PENGEMBANGAN POTENSI PERTANIAN, KESEHATAN DAN SOSIAL DARI NAGARI PANDAM GADANG KECAMATAN GUNUNG OMEH - Oknovia Susanti; Oktafiandes Oktafiandes; Dessy Yunita Sulaiman (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The purpose of the activity is to use the knowledge gained during the lecture period to be applied to the community, especially those in remote areas. This activity was carried out at Pandam Gadang, which involved 26 students. Pandam Gadang is a Nagari located in Gunuang Omeh District, Limapuluh Kota Regency. Gunuang Omeh District consists of 3 Nagari, namely Pandam Gadang, Koto Tinggi, and Talang Anau. Pandam Gadang consists of six jorongs, namely Jorong Koto Panjang, Jorong Kampuang Gaduang, Jorong Kampuang Patai, Jorong Ikan Banyak, Jorong Koto Marapak, Jorong Sungai Mangkirai. The problems that are often found in Nagari Pandam Gadang are agricultural problems such as pests and plant diseases and the remaining results of sorting oranges, which reduce productivity in agriculture. Gunuang Omeh sub-district is a district that is famous for its sweet oranges, 95% of the livelihoods of the residents of Nagari Pandam Gadang are farmers, so there are many work programs that students can carry out to improve agriculture in Nagari Pandam Gadang. The implementation of this activity uses training methods, socialization of benefits, and the materials needed and how to make them. The activity results are processing the remaining acidic citrus, which will be processed into orange-flavored jelly candy. Apart from being a new Nagari product, processing these leftover sour oranges can also be a selling point at a more economical price and good for health. It is hoped that Nagari Pandam Gadang will carry out evaluation activities on agricultural products or the obstacles faced every month to maximize agricultural production.